2007
DOI: 10.1007/s10832-007-9127-1
|View full text |Cite
|
Sign up to set email alerts
|

Glass-ceramics of barium strontium titanate for high energy density capacitors

Abstract: Barium strontium titanate glass-ceramics were successfully produced with one major crystalline phase when Al 2 O 3 was added to the melt. A dielectric constant of 1000 and a breakdown strength of 800 kV/cm was achieved; however the energy density was only measured to be 0.3-0.9 J/cm 3 . These energy density values were lower than anticipated due to the presence of dendrites and pores in the microstructure. Using BaF 2 as a refining agent improved the microstructure and doubled the energy density for BST 80/20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(81 citation statements)
references
References 12 publications
1
77
0
Order By: Relevance
“…Their properties have been exploited by Sandia National Lab and other research labs to fabricate high energy density capacitors for neutron generators and power electronic inverter applications (Tuttle et al 2001, Campbell et al 2002. The hybridization of linear and nonlinear dielectric ceramics was also investigated by TRS Technologies, The Pennsylvania State University and Naval Research Laboratory (Hackenberger et al 2010, Gorzkowski et al 2007). Glass was added into ferroelectric ceramics to improve sintering behavior and to reach high density, however, the defects and microstructural control in the process created difficulties in reaching high breakdown strength and energy density.…”
Section: High Temperature Dielectric Materialsmentioning
confidence: 99%
“…Their properties have been exploited by Sandia National Lab and other research labs to fabricate high energy density capacitors for neutron generators and power electronic inverter applications (Tuttle et al 2001, Campbell et al 2002. The hybridization of linear and nonlinear dielectric ceramics was also investigated by TRS Technologies, The Pennsylvania State University and Naval Research Laboratory (Hackenberger et al 2010, Gorzkowski et al 2007). Glass was added into ferroelectric ceramics to improve sintering behavior and to reach high density, however, the defects and microstructural control in the process created difficulties in reaching high breakdown strength and energy density.…”
Section: High Temperature Dielectric Materialsmentioning
confidence: 99%
“…Its desirable high dielectric constant, low dielectric losses, strong remnant polarization and low current leakage has been attractive for its fundamental research, and the material could be used for various applications such as dynamic random, access memory, ceramic capacitors, pyroelectric sensors, infrared detectors, chemical sensor, biosensor, microwave devices and optoelectronic applications in recent years [1][2][3] . With the intensive study on BST material, a large quantity of tentative exploration on ceramic, film, composite and doping vario-property of BST have been completed [4][5][6] . However, most of the experiments of BST focused on the properties in electrical and microwave frequency [7] .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the dielectric constant is 10 000 in bariumaluminosilicate system, but the replacement of aluminosilicate with borosilicate enhances the dielectric constant up to 12 000. BST glass ceramics in Al 2 O 3 addition make the dielectric constant of 1000 and breakdown strength of 800 kV/cm [10,11]. The replacement of AlF 3 by Ga 2 O 3 in glass ceramic system 60(Ba 0.7 Sr 0.3 )TiO 3 -25SiO 2 -15AlF 3 have enhanced the crystallization, while Bi 2 O 3 retards the crystallization.…”
Section: Introductionmentioning
confidence: 99%